2019 Ejtm Special on Muscle Fascia - Carla Stecco; Raffaele De Caro (PAGEPress Publications, 2019)
For many years the fasciae have been considered by the anatomists only as a "white envelope for the muscles", that is generally removed in anatomical tables, to recognize muscle nerves and vessels. This is one of the reasons that different descriptions of the fasciae exist. On the other hand, in the last years the fasciae and their properties are becoming of central importance to clinicians practicing in various conventional and alternative therapies. The results from the worldwide research activities constitute a body of significant and important data, but this clinical interest is not supported by in-depth comprehension to how integrate the new knowledge about fasciae with the classical biomechanical models based on muscles, tendons and bones. To close this gap an Ejtm Special on "Muscle Fascia" will be published September 30, 2019, but the typescripts will be added to the Ejtm Early Release list as soon as all authors will approve their Epub papers. Deadline for original articles and reviews is June 1st, 2019, but the Editors hope that authors submit their typescripts much earlier.